Repeated Retrieval Impacts Memory for Both Original Event and Post-Event Information - Wulff, Alia. (Tufts University. Tisch Library., 2023)
Thesis (Ph.D.)--Tufts University, 2023.; Submitted to the Dept. of Psychology.; Advisor: Ayanna Thomas.; Committee: Holly Taylor, Heather Urry, and Henry Otgaar.; Keyword: Psychology.